Energy recovery from wastewater in Mexico: A systematic review - Ortiz-Sánchez, M. Fabrizio; Cuevas-Rodriguez, Germán (Frontiers in Environmental Science, 2023)
The usage of fossil fuels to generate energy and the lack of wastewater treatment in Mexico are two issues that can be addressed at the same time while developing wastewater treatment technologies that incorporate energy recovery in their process train. We carried out a systematic review based on the PRISMA methodology to identify and review studies regarding energy recovery using wastewater as a substrate in Mexico. Peer-reviewed papers were identified through Scopus, Web of Knowledge, and Google Scholar, using a timeframe of 22 years that represented from 2000 to 2022. After applying the selection criteria, we identified 31 studies to be included in the final review, starting from 2007. The kind of energy product, type of technology used, substrate wastewater, amount of energy produced, and main parameters for the operation of the technology were extracted from the papers. The results show that methane is the most researched energy recovery product from wastewater, followed by hydrogen and electricity, and the technology used to archive it is an up-flow anaerobic sludge bed (UASB) reactor to produce methane and hydrogen. In addition, microbial fuel cells (MFCs) were preferred to produce electricity. According to our data, more energy per kgCOD removed could be obtained with methane-recovering technologies in the Mexican peer-reviewed studies compared with hydrogen recovery and electricity production.